Distributed voltage control in an islanded microgrid system with uncertainties - Png, Juliana Hui Min (Nanyang Technological University, 2022)
In recent years, renewable energy sources are heavy relied upon to reduce carbon emission and reducing the cost of energy. A microgrid is a local energy grid which can be operated in both islanded and grid-connected mode. While microgrids have many advantages, there are still challenges faced such as frequency and voltage fluctuations. This paper will be focusing on voltage restoration of the secondary control of a distributed AC microgrid system. Implementing an adaptive backstepping control method to solve the voltage fluctuation problem more efficiently compared to an adaptive fuzzy sliding mode controller. MATLAB Simulink will be used to design an islanded AC microgrid with 4 distributed generators in the sight of unknown parameters like resistances for the chosen advanced control method, adaptive backstepping control. The simulation results are successful in terms of voltage restoration. Keywords: voltage restoration; distributed AC microgrid; adaptive backstepping control; adaptive fuzzy sliding mode controller